2011
DOI: 10.1021/bm2016515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEG and mPEG-Anthracene on tRNA Aggregation and Particle Formation

Abstract: Poly(ethylene glycol) (PEG) and its derivatives are synthetic polymers with major applications in gene and drug delivery systems. Synthetic polymers are also used to transport miRNA and siRNA in vitro. We studied the interaction of tRNA with several PEGs of different compositions, such as PEG 3350, PEG 6000, and mPEG-anthracene under physiological conditions. FTIR, UV−visible, CD, and fluorescence spectroscopic methods as well as atomic force microscopy (AFM) were used to analyze the PEG binding mode, the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…2A and B). Similar aggregation and particle formation were observed for tRNA upon complexation with other ligands [27][28][29][30][31].…”
Section: Spectra and Trna Conformationsupporting
confidence: 73%
See 1 more Smart Citation
“…2A and B). Similar aggregation and particle formation were observed for tRNA upon complexation with other ligands [27][28][29][30][31].…”
Section: Spectra and Trna Conformationsupporting
confidence: 73%
“…1A-C, diff., 1 mM). The polyphenol-base bindings are via guanine and adenine N7 and uracil O2 atoms [27][28][29][30][31].…”
Section: Binding Analysis Of Polyphenol-trna Complexes By Ftir Spectrmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], were prepared with a fixed final DNA concentration of 50 µg/mL and a total volume of 100 µL. Each mixture was incubated with DNaseI (5 U/µg of plasmid DNA) at 37°C for 1 hour.…”
Section: Stability Of Activated Egf-dendriplexesmentioning
confidence: 99%
“…6,[8][9][10][11] Their applications in drug delivery helped optimize in vivo distribution of drugs and passive tumor targeting through the EPR effect. 4 By taking advantage of the modifiable amino groups on the surface, researchers have conjugated different ligands, such as biotinavidin, 12 lysine, 13,14 and PEG [15][16][17] onto PAMAM surfaces to enhance transfection efficiency in vivo and in vitro. Recent studies reveal that PAMAM dendrimers activated by timecontrolled heat treatment can make dendriplexes more flexible and exhibit higher transfection efficiency, 18,19 even though such activation may cause the sacrifice of superficial charges by losing some branches of the dendrimer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. PEGylation of synthetic polymers such as dendrimers is shown to reduce toxicity and increase biocompatibility and DNA Transfection [6,7,9].…”
Section: Introductionmentioning
confidence: 99%